Phase Relationship Between Cerebral Blood Flow Velocity and Blood Pressure: A Clinical Test of Autoregulation - Diehl, Rolf R.; Linden, Dieter; Lücke, Dorothee; Berlit, Peter (Stroke (1970), 1995)
Background and Purpose This study investigates the usefulness, as a test of dynamic autoregulation, of phase shift angle analysis between oscillations in cerebral blood flow velocity (CBFV) and in arterial blood pressure (ABP) during deep breathing. Methods Fifty healthy volunteers, 20 patients with occlusive cerebrovascular diseases (OCD), and 10 patients with arteriovenous malformations (AVM) took part in the study. All subjects received transcranial Doppler monitoring of both middle cerebral arteries (MCAs). In addition, continuous blood pressure monitoring was performed with the use of noninvasive servo-controlled infrared finger plethysmography during deep breathing at a rate of 6/min. With the use of a high-pass filter model of autoregulation, autoregulation was quantified as phase shift angle between oscillations in CBFV and ABP at a frequency of 6/min. A phase shift angle of 0° indicates total absence of autoregulation, while 90° can be gauged as optimal autoregulation. In addition, vasomotor reactivity of both MCAs to CO 2 stimulation was assessed among patients and calculated as percent increase in CBFV per millimeter of mercury of increase in CO 2 . Results All normal subjects showed positive phase shift angles between CBFV and ABP (mean±SD, 70.5±29.8°). OCD patients presented with significantly decreased phase shift angles for the MCA only on the pathological side (51.7±35.1°; P <.05). Patients with AVM showed significantly reduced phase shift angles on both the affected side (26.8±13.5°; P <.001) and the unaffected side (40.6±26.6°; P <.01). In patients’ groups, phase shift angle and vasomotor reactivity correlated significantly ( r =.66; P <.001) after results from all MCAs were pooled. Conclusions Results confirm the high-pass filter model of cerebral autoregulation: Normal subjects showed predicted positive phase shift angles between CBFV and ABP oscillations. Patients with expected autoregulatory disturbances showed significant decreases in phase shift angles. Close correlations existed between autoregulation and CO 2 -induced vasomotor reactivity.